THE IMPORTANCE OF CHILDREN’S RIGHTS IN EDUCATING A SPIRITUALLY COMPLETE AND PHYSICALLY HEALTHY GENERATION - Norieva , Aziza Jasur qizi (Educational Research in Universal Sciences, 2023)
In the article, consideration of the rights and freedoms of a spiritually mature and physically healthy generation, as well as the main directions established in this regard, are presented. it is recognized that every pedagogue should know these rights and freedoms in the process of education and upbringing of children.